Examining Teachers’ Perception On The Impact Of Ict On Basic School Students’ Academic Performance: A Study Of Afienya Circuit - Kennedy, Darko Kennedy; Kuupille, Fredrick; Segbefia, Samuel Kwabla (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
Schooling is crucial to a country’s socioeconomic progress. No nation can progress without education, so every nation must provide a quality education so its population can participate in development. Raising the population’s education level is key to economic growth. The researchers were interested in the topic since using computers at a fundamental level can lead to better schooling. ICT in education has three purposes: teaching, administration, and personal (Kellenberger & Hendricks, 2000). A descriptive survey research design was used. Afienya circuits. The survey questionnaire analysis complemented the interview and document analysis. Using computers in primary schools in Mobole-Afienya Circuit encourages open learning, removes distance and time between teachers and students, supports the practice of previously taught concepts, and helps learners acquire concepts and skills like word recognition and vocabulary building. Most teachers in the Mobole-Afienya circuit believe that computers aid in content production, and research may be used for pedagogical activities and increase successful teaching. Most respondents feel computers may improve teaching and learning in elementary schools. Insufficient computers, a shortage of electricity and unpredictable power supply, poor internet connectivity, and insufficient teacher training and refresher courses were the primary problems facing computer use in public elementary schools, according to the report.